An updated list of cryptobenthic fishes (Syngnathidae, Gobiidae, Gobiesocidae, Tripterygiidae, Blenniidae, Scorpaenidae) in the IUSHM fish collection - Nur Bikem KESICI; Cem DALYAN (Turkish Journal of Bioscience and Collections, 2018)
In the Mediterranean Sea, data on the cryptobenthic fishes are limited and the number of specimens kept in museum collections is fragmentary. Hydrobiology Museum of Istanbul University, the only documented fish collection of Turkey, accommodates only a few specimens among these cryptobenthic species. The purpose of this paper is to enrich the number of collections in the Hydrobiology Museum and to exhibit an updated list of cryptobenthic fishes collected from the Turkish waters. A total of 164 specimens belonging to 18 species have recently been added to the collection. In total, the number of specimens in the IUSHM reached up to 219 with 32 species belonging to six families.